The naked island - Hayashi, Hikaru 1931-2012 (The Criterion Collection, 2016)
The international breakthrough for one of Japan's most innovative filmmakers, who went on to make such other marvelous movies as Onibaba and Kuroneko. It follows a family whose home is on a tiny, remote island off the coast of Japan. They must row a great distance to another shore, collect water from a well in buckets, and row back to their island, a nearly backbreaking task essential for the survival of these people and their land
Original: Japan 1960
Bildformat 2.35:1
DVD special edition restoration: video introduction by director Kaneto Shindo, recorded for a 2011 retrospective of his work ; audio commentary recorded in 2000, featuring Shindo and composer Hikaru Hayashi ; new appreciation of the film by actor Benicio Del Toro ; new interview with film scholar Akira Mizuta Lippit ; trailer ; plus: an essay by film scholar Haden Guest
Keywords: Farmers / Japan / Drama; Islands / Japan / Drama; Film; DVD-Video